Analysis of Islamic Political Economic Thought During the Khulafa Arrosyidin Period - Samsul Arifin; Rania Ningsih; Vifin Nadzary Al Awaly; Mashudi (Penerbit Hellow Pustaka, 2025)
This study aims to review how Islamic political economic thinking was during the time of the Khulafaur Rasyidin, consisting of Abu Bakar as-Siddiq, Umar bin Khattab, Utsman bin Affan, and Ali bin Abi Thalib. In their government, Islamic economic policies were implemented based on the Qur'an and Hadith, aiming to achieve the welfare of the people. This study was conducted using a library research method or approach or a qualitative approach. Literature study is a series of activities related to the method of collecting library data, reading and recording and processing research materials. The results of the study show that the application of Islamic economics by the Khulafaur Rasyidin succeeded in creating economic stability and a just government, even though it was colored by internal political conflict.